Effect of visual feedback on the performance of the star excursion balance test. (July 2019) - Wan, Yi; Davies, Jennifer L; Button, Kate; Al-Amri, Mohammad
Introduction: Visual feedback is an effective method to enhance postural and balance control in clinical and sports training. The aim of this study was to explore the effect of real-time visual feedback provided by a video camera on the performance of a dynamic balance test, which is the star excursion balance test in healthy subjects. Methods: We compared the performance of the star excursion balance test using the maximum reach distance in 20 healthy participants (10 male and 10 female, 26.8 ± 3.7 years) under two conditions: without feedback and whilst they viewed their movements in real-time on a screen in front of them via a video camera. Results: The results showed that real-time visual feedback had a significant effect on maximum reach distance of the star excursion balance test in the posterolateral direction (P < 0.001). There was a non-significant increase in the maximum reach distance in the anterior and posteromedial directions. Conclusion: The result indicates that the real-time visual feedback appears to be an effective means for improving the performance of the star excursion balance test in the posterolateral direction, and may be a promising tool for clinical rehabilitation and athlete training to enhance dynamic postural control.